The Political Economy of an Emerging Global Power - Casanova, L. author. aut Link
XVIII, 202 p.
Keywords: Is Brazil ready to take its place among the world's leading powers? The authors examine Brazil's hard power and soft power resources, assessing the challenges the country will need to overcome in order to build its own "Brazilian dream" and project itself on the international stage.